2021
DOI: 10.7454/mst.v25i1.3677
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Hollow-core Slab Containing Waste PET Bottles

Abstract: This study investigated the utilization of plastic-waste concrete as an effort to reduce urban waste problems. The waste plastic bottles were utilized to form the hollows of the hollow-core slabs (HCSs). The bottles were made of polyethylene terephthalate (PET). As a part of green research to reuse waste material, shredded PET was also added to the concrete mixture to improve the HCS strength. The cast-in-site HCS could be constructed without any difficulties. Three parameters were investigated: the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…It can therefore be said that the incorporation of plastic bottles filled with PKS performed better in terms of flexural strength than conventional sod slabs of the same concrete properties. Previous research on bubble deck slabs has found that the plastic formers reduce the strength of the slabs [53,55]. Furthermore, the increased flexural strength of the PKSfilled bottle slabs could be attributed to the PKS filling the voids created by the plastic bottles in the slab, thereby assisting in the load carrying capacities of the slabs.…”
Section: Flexural Strengthmentioning
confidence: 96%
See 1 more Smart Citation
“…It can therefore be said that the incorporation of plastic bottles filled with PKS performed better in terms of flexural strength than conventional sod slabs of the same concrete properties. Previous research on bubble deck slabs has found that the plastic formers reduce the strength of the slabs [53,55]. Furthermore, the increased flexural strength of the PKSfilled bottle slabs could be attributed to the PKS filling the voids created by the plastic bottles in the slab, thereby assisting in the load carrying capacities of the slabs.…”
Section: Flexural Strengthmentioning
confidence: 96%
“…The flexural test report indicates that the load carrying capacity, flexural strength, and deflection of the bubble deck slab reinforced with FRP were 18% greater than those of the conventional slab. Orientilize et al (2021) [55] studied experimentally a Hollow-core slab (HCS) containing waste PET bottles as an effort to reduce urban waste problems. The specimen had a length, width, and thickness of 1750 mm, 600 mm, and 150 mm, respectively.…”
Section: Studies On Bubble Deck Slabs Employed In Constructionmentioning
confidence: 99%
“…Furthermore, voids can be used as a service path for mechanical and electrical work. Di erent con gurations have been formulated to produce voids inside the concrete structural elements such as bubbles [5][6][7][8][9][10][11][12] and pipes [13][14][15]. However, these methods of voids are almost expensive and required complicated formwork to install.…”
Section: Introductionmentioning
confidence: 99%
“…For one-way slab, very little research had been conducted on plastic waste plastic bottles to form voids. Orientilize et al [11] investigated the effects of using waste plastic bottles as voids to form a hollow core one-way slab on the flexural behavior. ree parametric studies were conducted: the content of voids, chopped PET, and steel fiber content.…”
Section: Introductionmentioning
confidence: 99%